2008
DOI: 10.1590/s0100-879x2008005000025
|View full text |Cite
|
Sign up to set email alerts
|

Fetal development of regulatory mechanisms for body fluid homeostasis

Abstract: The balance of body fluids is critical to health and the development of diseases. Although quite a few review papers have shown that several mechanisms, including hormonal and behavioral regulation, play an important role in body fluid homeostasis in adults, there is limited information on the development of regulatory mechanisms for fetal body fluid balance. Hormonal, renal, and behavioral control of body fluids function to some extent in utero. Hormonal mechanisms including the renin-angiotensin system, aldo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
0
8
0
2
Order By: Relevance
“…In regard to the salivary glands, Fanni et al [28] indicated that thymosin â10 has a role in their organogenesis. Based on the established data about ANP role in rat brain development [15,16,22], our results showing ANP presence early during the development of human parotid gland suggest that ANP might be involved in parotid gland's maturation similarly as in the nervous system.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In regard to the salivary glands, Fanni et al [28] indicated that thymosin â10 has a role in their organogenesis. Based on the established data about ANP role in rat brain development [15,16,22], our results showing ANP presence early during the development of human parotid gland suggest that ANP might be involved in parotid gland's maturation similarly as in the nervous system.…”
Section: Discussionmentioning
confidence: 55%
“…The literature data on the ANP-ontogeny refer to heart [13][14][15], brain [16][17][18], and lung [19]. The morphology of developing salivary glands was described in rat [20,21], mouse [22], miniature pig [23], and in humans [24].…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that maternal water deprivation significantly reduced fetal urine volume associated with an increase of urine osmolality at near‐term. One of the mechanisms behind this phenomenon could be aldosterone that is critical in regulation of fetal renal excretion (Guan et al, 2008; Mann et al, 1999). Notably, fetal plasma aldosterone was significantly increased following exposure to maternal water deprivation in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…They also concluded that no fetal organ controls the fetal fl uid volume, and the main determinants in fl uid balance are cardiac, circulatory, renal, and placental properties [ 28 ].…”
Section: Fetal Fluid Dynamicsmentioning
confidence: 99%